A distinct small RNA pathway silences selfish genetic elements in the germline. - Vagin, V.V.; Sigova, A.; Li, C.; Seitz, H.; Gvozdev, V.; Zamore, P.D. (Science, 2006)
In the Drosophila germline, repeat-associated small interfering RNAs (rasiRNAs) ensure genomic stability by silencing endogenous selfish genetic elements such as retrotransposons and repetitive sequences. Whereas small interfering RNAs (siRNAs) derive from both the sense and antisense strands of their double-stranded RNA precursors, rasiRNAs arise mainly from the antisense strand. rasiRNA production appears not to require Dicer-1, which makes microRNAs (miRNAs), or Dicer-2, which makes siRNAs, and rasiRNAs lack the 2',3' hydroxy termini characteristic of animal siRNA and miRNA. Unlike siRNAs and miRNAs, rasiRNAs function through the Piwi, rather than the Ago, Argonaute protein subfamily. Our data suggest that rasiRNAs protect the fly germline through a silencing mechanism distinct from both the miRNA and RNA interference pathways.